1973
DOI: 10.1007/bf01985435
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, distribution, and metabolism of inhaled ethylmercuric chloride in the rat

Abstract: COMMUNICATED BY LOUIS LYKKENThe uptake and the tissue distribution of ethylmercuric chloride (EMC) by inhalation and oral administration were studied in adult female rats. The pulmonary uptake of EMC linearly increases with the time of exposure and is proportional to the concentration of EMC vapor. With the exception of stomach, intestine, and hair, the tissue distribution of 2 o 3 Hg from pulmonary uptake is quite similar to that from oral administration. The biological halflife of EMC in the organs is longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
2007
2007

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…They concluded that MeHg does not appear to be a good model for EtHg-containing compounds. In the rat model, Fang and Fallin 29 showed that nonenteral (inhaled) uptake of EtHg had a higher tissue distribution of 203 Hg (stomach, intestine, and hair) and a longer biological half-life of EtHg in organs 21 than oral administration. Acute exposure to inhaled EtHg, besides causing a much higher overall fetal death rate than orally administered EtHg, also caused a decrease in the number of offspring per litter.…”
Section: Metabolism Of Pure Injected Thimerosal Ethgmentioning
confidence: 99%
“…They concluded that MeHg does not appear to be a good model for EtHg-containing compounds. In the rat model, Fang and Fallin 29 showed that nonenteral (inhaled) uptake of EtHg had a higher tissue distribution of 203 Hg (stomach, intestine, and hair) and a longer biological half-life of EtHg in organs 21 than oral administration. Acute exposure to inhaled EtHg, besides causing a much higher overall fetal death rate than orally administered EtHg, also caused a decrease in the number of offspring per litter.…”
Section: Metabolism Of Pure Injected Thimerosal Ethgmentioning
confidence: 99%